The Development of Problem Based Learning Device for Junior High School Natural Science Class for Learning Substance Pressure and its Daily Use Material - Efrida Welni; A Fauzi; Usmeldi Usmeldi (Postgraduate School, Universitas Negeri Padang, 2020)
This research was purpoted to develop a valid, practical and effective learning devices based on problem-based learning model especially for substance pressure materials. The development model used was 4-D model from Sivasailam Thiagarajan. The research data are validity data, practicality data, and effectiveness data. The research instruments were validation sheets, practicality sheets, and effectiveness sheets. The data analysis technique used is a descriptive analysis. The results of the study are the science learning tools of SMP based on the learning model of problem-based learning on material pressure and its application in everyday life that is valid, practical and effective.